2022
DOI: 10.36418/dev.v3i10.199
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Leucine Intake with Serum Prolactin and Breast Milk Protein Levels in Breastfeeding Women

Abstract: Breast milk is the best choice food for a baby’s growth and development of infants at some point of the primary 6 months of life. Fulfillment of nutrition during breastfeeding is an important requirement, one of which is the intake of the amino acid leucine which is said to affect prolactin as a regulator of breast milk production and protein synthesis in breast milk. This can support the quality and quantity of breast milk to meet the nutritional needs of infants support infant growth and development and redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In this study, six essential amino acids from the mother's diet correlated with total milk protein. These amino acids are isoleucine (Ile), leucine (Leu) [51], lysine (Lys), phenylalanine (Phe), methionine (Met), and valine (Val). However, threonine (Thr) and tryptophan (Trp) showed no correlation with total milk protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, six essential amino acids from the mother's diet correlated with total milk protein. These amino acids are isoleucine (Ile), leucine (Leu) [51], lysine (Lys), phenylalanine (Phe), methionine (Met), and valine (Val). However, threonine (Thr) and tryptophan (Trp) showed no correlation with total milk protein.…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of high-protein foods can elevate prolactin concentrations, and prolactin acts as a provider of amino acids through SNAT2 during the protein synthesis process in the mammary glands [14]. One of the proteins that has an important role is leucine; leucine plays a significant role in regulating the expression of SNAT2 in the mammary glands, as well as in the liver and adipose tissue, during lactation [51]. Meanwhile, King et al (2021) found that methionine supplementation may decrease milk protein synthesis but can enhance the availability of other amino acids to fulfill the body's needs [55].…”
Section: Discussionmentioning
confidence: 99%